2017
DOI: 10.1002/2017gl074723
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for surface water ice in small‐scale cold traps and in three large craters at the north polar region of Mercury from the Mercury Laser Altimeter

Abstract: The Mercury Laser Altimeter (MLA) measured surface reflectance, rs, at 1064 nm. On Mercury, most water‐ice deposits have anomalously low rs values indicative of an insulating layer beneath which ice is buried. Previous detections of surface water ice (without an insulating layer) were limited to seven possible craters. Here we map rs in three additional permanently shadowed craters that host radar‐bright deposits. Each crater has a mean rs value >0.3, suggesting that water ice is exposed at the surface without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…As a consequence, surface temperatures in these regions are extremely low (i.e., less than 110 K) ( 1 3 ) and are limited only by heat flow from the interior and sunlight reflected from adjacent topography ( 4 6 ). These areas are predicted to act as cold traps that are capable of accumulating volatile compounds over time, supported by observations of water ice at the optical surface of polar shadowed locations on Mercury ( 7 9 ) and Ceres ( 10 , 11 ). There are a number of strong indications of the presence of water ice in similar cold traps at the lunar poles ( 12 14 ), but none are unambiguously diagnostic of surface-exposed water ice, and inferred locations of water ice from different methods are not always correlated.…”
mentioning
confidence: 75%
“…As a consequence, surface temperatures in these regions are extremely low (i.e., less than 110 K) ( 1 3 ) and are limited only by heat flow from the interior and sunlight reflected from adjacent topography ( 4 6 ). These areas are predicted to act as cold traps that are capable of accumulating volatile compounds over time, supported by observations of water ice at the optical surface of polar shadowed locations on Mercury ( 7 9 ) and Ceres ( 10 , 11 ). There are a number of strong indications of the presence of water ice in similar cold traps at the lunar poles ( 12 14 ), but none are unambiguously diagnostic of surface-exposed water ice, and inferred locations of water ice from different methods are not always correlated.…”
mentioning
confidence: 75%
“…Estimates of Mercury's water‐ice inventory range from ~10 16 to 10 18 g (Deutsch et al, ; Eke et al, ; Lawrence et al, ; Moses et al, ; Susorney et al, ). Recent studies have suggested that additional water‐ice reserves may exist in small‐scale cold traps distributed across rough, intercrater terrain in the polar regions (Deutsch et al, ; Neumann et al, ; Rubanenko et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The measured global high abundances of S 1 , Cl 2 , and K 5 reveal a significant surface record of volatile-bearing materials. Also, local polar H 2 O ice form deposits within numerous permanently shadowed crater interiors in the planet's polar regions [8][9][10] . Currently documented evidence of surface modifications due to the removal of volatiles includes Mercury's hollows, which are shallow, flat-floored, irregular, rimless depressions with bright interiors, and halos [11][12][13][14] .…”
mentioning
confidence: 99%